2019
DOI: 10.1097/sla.0000000000002663
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spotting as a Strategy to Identify High-Cost Surgical Populations

Abstract: We found that a subset of multimorbid patients was responsible for a disproportionate share of total Medicare spending, but the individual components of spending vary by procedure. These findings suggest that targeting high-cost Medicare patients (ie, hot spotting) for cost containment efforts would be a potentially effective strategy to reduce costs in surgical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Typically, only costs of care based on the time around the surgical episode itself (eg, 30-day perioperative period) have been examined. 1,2,5,[13][14][15][16][17][18][19][20]22,23,40 Although previous studies have identified super-utilizers at the time of surgical intervention, data on the longer-term relationship of these patients with the health care system have not been well examined. To our knowledge, no study has longitudinally analyzed superutilization following surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, only costs of care based on the time around the surgical episode itself (eg, 30-day perioperative period) have been examined. 1,2,5,[13][14][15][16][17][18][19][20]22,23,40 Although previous studies have identified super-utilizers at the time of surgical intervention, data on the longer-term relationship of these patients with the health care system have not been well examined. To our knowledge, no study has longitudinally analyzed superutilization following surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…ising health care costs have increased awareness around super-utilizers-a small subset of the total patient population who consume a disproportionate amount of health care resources. [1][2][3][4][5][6][7][8][9][10] Typically defined as the top 5% of health care users, super-utilizers are responsible for an estimated 40% to 55% of all health care costs. 7, [9][10][11] By proactively identifying those patients, a process known as "hot spotting," targeted efforts may improve quality of care and outcomes as well as decrease the cost burden on the health care system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ACOs must know who their beneficiaries are if they are to optimize surgical costs, in particular if they wish to prospectively identify high-cost surgical patients for intervention. 33,34 Recently, prospective beneficiary assignment has been implemented, but its effects remain to be seen. In particular, there may be important interactions between beneficiary assignment to an ACO and hospital ACO affiliation that can ultimately influence quality and cost of surgical care.…”
Section: Discussionmentioning
confidence: 99%